Parental Perception of Preschool Children's Mental Health and Synchronous Online Education Effectiveness in Knowledge Enhancement - Merita Arini; Warih Andan Puspitosari; Harumi Iring Primastuti; Wan Hasliza Wan Mamat (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Mental health in children is crucial for their growth, development, and academic achievement. The high prevalence of mental health disorders in children necessitates efforts to enhance parental knowledge via more accessible channels. This study aims to evaluate parental perceptions of children's mental health and assess the impact of online mental health education on parental knowledge. Methods: A quasi-experimental design using a single-group pre-test and post-test method was conducted with 52 participants. The intervention consisted of synchronouz mental health education delivered via an online meeting platform, with data collected through pre- and post-test evaluations using Google Forms. Results: 53.8% of parents were concerned about their child's mental health, yet 40.4% were unsure about their capacity to recognize symptoms, and 78.8% had never conducted early screening. The Wilcoxon Signed-Rank Test indicated no statistically significant difference in knowledge scores before and after the intervention (p=0.177). However, the mean score increased slightly from 6.71 (SD=1.05) in the pre-test to 6.98 (SD=1.29) in the post-test. The effect size (r = -0.64, 95% CI = [-0.91, -0.37]) shows an impact classified as moderate to large. Conclusion: While many parents are concerned for their children's mental health, many cannot recognize symptoms and have not undertaken early screening. Although statistical significance was not achieved, the observed effect size and knowledge improvement in specific individuals highlights online education's potential to enhance parental understanding of children's mental health. It is imperative to advance the exploration of interactive and adaptable learning strategies to maximize the effectiveness of educational interventions.